The Commutator of Two Fuzzy Subsets - Tawfiq, L. N. M.; Shihab, R. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper we introduce the idea of the commutator of two fuzzy subsets of a group and study the concept of the commutator of two fuzzy subsets of a group .We introduce and study some of its properties .